Implementation of Legal Protection and Factors Hindring Child Protection: A Case Study of South Sumatra Province - Johan Edi Nepri; Pasiska Pasiska (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research aims to understand how the implementation of child protection laws increases legal protection for child victims of sexual violence and to better understand what factors hinder the implementation of these laws. In this regard, This legal protection needs to be studied to understand the role of children's rights and protection issues regarding children's rights in South Sumatera Province. This research is a type of doctrinal legal research by collecting (documenting) secondary data. in Law no. 35 of 2014 Regarding the Protection of Children who are victims of sexual violence, Legal protection for children from a human rights perspective cannot be implemented because the government has not carried out several of its obligations in fulfilling children's rights so that there are still legal violations against children